2013
DOI: 10.1139/cjfas-2012-0347
|View full text |Cite
|
Sign up to set email alerts
|

Salmon-mediated nutrient flux in selected streams of the Columbia River basin, USA

Abstract: Salmon provide an important resource subsidy and linkage between marine and land-based ecosystems. This flow of energy and nutrients is not unidirectional (i.e., upstream only); in addition to passive nutrient export via stream flow, juvenile emigrants actively export nutrients from freshwater environments. In some cases, nutrient export can exceed import. We evaluated nutrient fluxes in streams across central Idaho, USA, using Chinook salmon (Oncorhynchus tshawytscha) adult escapement and juvenile production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Salmon deliver N, P, and a variety of other trace nutrients and minerals to ecosystems, and ultimately may affect the nutrient limitation status of organisms in recipient ecosystems by influencing the ratios of available N and P. Moreover, the effects of delivered nutrients will vary depending on their form; for example, ammonium-N excreted during spawning will be much more bioavailable than P delivered as bone in a salmon carcass. Finally, nutrient inputs must also be considered in terms of their balance against nutrient export, including those from outmigrating juvenile salmon Kohler et al 2013). For example, Gross et al (1998) estimated that historic contributions of phosphorus from sockeye salmon migrations only comprised 3 % of the total annual P budget for Redfish Lake (Idaho, USA), in part because of export by smolts.…”
Section: Are the Ecological Effects Of Salmon Ubiquitous And Homogenementioning
confidence: 99%
“…Salmon deliver N, P, and a variety of other trace nutrients and minerals to ecosystems, and ultimately may affect the nutrient limitation status of organisms in recipient ecosystems by influencing the ratios of available N and P. Moreover, the effects of delivered nutrients will vary depending on their form; for example, ammonium-N excreted during spawning will be much more bioavailable than P delivered as bone in a salmon carcass. Finally, nutrient inputs must also be considered in terms of their balance against nutrient export, including those from outmigrating juvenile salmon Kohler et al 2013). For example, Gross et al (1998) estimated that historic contributions of phosphorus from sockeye salmon migrations only comprised 3 % of the total annual P budget for Redfish Lake (Idaho, USA), in part because of export by smolts.…”
Section: Are the Ecological Effects Of Salmon Ubiquitous And Homogenementioning
confidence: 99%
“…There is a general consensus that Pacific salmon populations are unconditional sources of nutrients to their natal streams Schindler 2004, Scheuerell et al 2005) or should be (Moore et al 2011, Kohler et al 2013). In our study on Atlantic salmon over a 20-year period, flow of P into freshwater via adult salmon and the flow of P back to the ocean via smolts was almost perfectly efficient in Campbellton and Western Arm, meaning that adult salmon deposited nearly the same amount of P that was exported by smolts.…”
Section: Phosphorus Fluxmentioning
confidence: 99%
“…Annual nitrogen and phosphorus imports by adults can be substantial at the watershed scale (e.g., Gresh et al 2000, Moore andSchindler 2004). In the last decade, numerous studies have concluded that semelparous Pacific salmon are net sources of nitrogen and phosphorus to their natal watersheds when populations are considered healthy (e.g., Moore and Schindler 2004, Scheuerell et al 2005, Kohler et al 2013. Anadromous Atlantic salmon (Salmo salar L.) are iteroparous and the majority of adults spawning in late autumn survive to overwinter in freshwater and return to the ocean as kelts (i.e., post-spawn adults).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable body of research has investigated the effects of the salmon's unique life history, which couples offshore marine productivity to coastal ecosystems (Gende et al 2002, Naiman et al 2002. However, the net effects of spawning salmon can vary (Harding et al 2014); salmon can subsidize freshwater and riparian habitats through excretion and egg and carcass deposition (Kline et al 1990, Cederholm et al 1999, Janetski et al 2009, and can export nutrients with juvenile emigration and disturbance as adults dig and defend nests (Moore et al 2007, Kohler et al 2013. Although considerable amounts of salmon-derived nutrients imported into coastal watersheds are retained, large proportions are also exported downstream to estuaries (Gende et al 2004, Mitchell and Lamberti 2005, Cak et al 2008.…”
Section: Introductionmentioning
confidence: 99%